The Representation of the matrialineal tribe in Indonesia: A cultural study of selected Minangkabau Novels - Lulu Fahkrunisa; Mark Anthony G Moyano; Michael S. Naidas (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2026)
This study examines the evolving representation of gender roles and cultural identity within the Minangkabau matrilineal system through a critical analysis of three seminal Indonesian novels three Indonesian novels: Siti Nurbaya, Never the Twain, and The Land of Five Towers. Employing a qualitative-interpretive method grounded in Gramsci’s theory of cultural hegemony, the research analyzes how power relations, traditions, and ideological negotiations are reflected across colonial and modern contexts. The findings reveal a significant transformation in gender representation. Women are initially portrayed as moral anchors bound by adat (customary law) and sacrifice, but later emerge as visionary figures who guide families toward a synthesis of tradition and modernity. Meanwhile, men negotiate their peripheral domestic role through merantau (migration), which functions as a counter-hegemonic strategy enabling them to gain intellectual and social capital. Furthermore, the study highlights the evolving relationship between adat and Islam, shifting from conflict toward a hybrid hegemony encapsulated in the philosophy Adat Basandi Syarak, Syarak Basandi Kitabullah. The study concludes that contemporary Minangkabau identity reflects a resilient integration of matrilineal tradition, Islamic values, and global modernity, as represented in literary discourse.